2002
DOI: 10.1097/00005373-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Outcomes in Trauma

Abstract: Although the incidence of pneumonia was not influenced by gender, female trauma patients had better outcomes than male patients in the younger age group. Outcome in the older age group was not gender-related. Our data support a gender-based difference in outcome after traumatic injuries in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 21 publications
8
85
1
3
Order By: Relevance
“…25,26 These findings may be related to recent results by Frink et al, 27 who reported that injured females in the ICU had fewer complications related to inflammatory response. It is difficult to compare the results of Frink and colleagues directly, however, because the complications measured in their study were not measured in the present research.…”
Section: Age Sex and Smokingsupporting
confidence: 53%
“…25,26 These findings may be related to recent results by Frink et al, 27 who reported that injured females in the ICU had fewer complications related to inflammatory response. It is difficult to compare the results of Frink and colleagues directly, however, because the complications measured in their study were not measured in the present research.…”
Section: Age Sex and Smokingsupporting
confidence: 53%
“…6,[10][11][12][13][14][15] Less is known about the influence of other demographic variables such as race/ethnicity and socioeconomic status. Critical care research 16,17 (nonspecific to trauma) has shown that African Americans and persons of low socioeconomic status have nearly twice the rates of sepsis, organ dysfunction, and sepsis-related mortality as do whites.…”
mentioning
confidence: 99%
“…We chose a clinical setting (young women undergoing a low stress standardized surgical procedure, i.e., laparoscopy for minor gynecological benign disease) which allowed us to investigate the effects of sevoflurane vs isoflurane, avoiding any interference by other factors which are known to affect hormonal response (age, sex, type and duration of surgery, blood loss, pain, vasoactive drugs, etc.). 8,[26][27][28][29][30] In this setting, we found that catecholamine levels were relatively unaffected by the choice of the main anesthetic drug: surgical stress caused a similar variation of serum catecholamines both in the isoflurane and in the sevoflurane group. Changes in circulating E reflect adrenal medullary activity, whereas changes in NE reflect the activity of the overall sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%